nep-iaf: A new e-mail service to stay up to date with working papers on international activities of firms - Wagner, Joachim (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2025)
This (very short) note introduces nep-iaf, a new e-mail service that helps researchers interested in international activities of firms to stay up to date with newly published working papers on firms’ international activities, e.g. export, import, foreign direct investment, offshoring, licensing, and any other types of cross-border activities. As part of RePEc, nep-iaf (or new economic papers – international activities of firms) is free. To subscribe simply go to https://nep.repec.org/nep-iaf
Keywords: International Trade; Export; Import; Foreign Direct Investment; Offshoring; International Licensing; Firm Level Data; 330 Wirtschaft